BUDIDAYA PADI YANG DIPANGKAS SECARA PERIODIC DAN DIBERI PUPUK KOMPOS Chromolaena odorata DAN ANALISIS USAHATANINYA - Jamilah Jamilah (Jurnal Ilmiah Pertanian, 2018)
The study titled " Rice Cultivation pruned periodically And Fertilized By Chromolaena odorata Compost (CC)" had been carried out during the second period of the growing season, the first season (MT1), and the second season (MT2), was ratoon. The aimed was to reach maximum forage and yield of rice pruned periodically fertilized by C.odorata compost. The experiments were conducted in Split-plot, which was arranged in a completely randomized design. The main plot consists of two levels; not pruned (P0) and pruned (P1). The subplot was three doses of CC, namely; 5 Mg ha-1 (B1); 7.5 Mg ha-1 (B2) and 10 Mg ha-1 (B3). The parameters observed; plant height, maximum and productive tiller, the production of forage, the percentage of empty grain, grain weight. Data were analyzed statistically if the real effect of treatment then continued with Honestly Significant Difference test α 5%. The results proved that there was no influence C.odorata compost, on the growth and yield of rice both at the MT1 and MT2. Forage fodder (HMT) decreased acquisition on MT2 (ratoon) up to 50% compared to HMT at MT1. An increase in the empty grain to 4-fold in ratoon model (MT2) than MT1. From an economic perspective, there was a loss of farmers, pruning, until MT2, Rp. 2.9 million compared to plants that were not pruned but also be ratoon.